Graft function and renal protection with peritransplant systemic dexmedetomidine in kidney and liver recipients: systematic review and meta-analysis of randomized controlled trials - Reichert, Martin; Willis, Franziska; Koch, Christian; Amati, Anca-Laura; Braun, Jacqueline; Weigand, Markus A.; Sander, Michael; Karakizlis, Hristos; Schneider, Martin; Hecker, Andreas; Justus Liebig University Giessen (My University, 2025)
This systematic review analyzed ten randomized controlled trials to assess the effects of dexmedetomidine during kidney and liver transplants. The study found that dexmedetomidine may reduce delayed graft function in deceased donor kidney transplants and living donor liver transplants, and decrease posttransplant acute kidney injury. Improvements in early postoperative serum creatinine and allograft function were noted in living donor liver transplants, but not in deceased donor liver transplants. Despite these benefits, there was no evidence of improved long-term allograft survival. More extensive trials are needed to confirm these findings and evaluate long-term outcomes.
Keywords: ddc:610